Proceedings of XII Multifrequency Behaviour of High Energy Cosmic Sources Workshop — PoS(MULTIF2017) 2018
DOI: 10.22323/1.306.0051
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Mass Black Holes: A Review

Abstract: Intermediate mass black holes (IMBHs) are an (as yet) elusive class of black holes that are expected to lie in the 10 2 − 10 5 M ⊙ range, between the firmly established stellar-mass black holes and 10 6 M ⊙ supermassive black holes. Predicted by a variety of theoretical models, IMBHs are the potential seeds of supermassive black holes and are expected to power some of the brightest extra-nuclear X-ray sources. This brief review is the result of a presentation and subsequent discussion of IMBHs that took place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 258 publications
(320 reference statements)
0
11
0
Order By: Relevance
“…In addition to the selection bias of more luminous host galaxies targeted for spectroscopy in the SDSS sample (see, e.g., discussions by Greene & Ho 2004 and Barth, Greene, & Ho 2008), the spectral and spatial resolution of telescopes (like the 5 m telescope used in the Palomar survey) lies right at the threshold of detecting the signatures of a slowly accreting black hole with a mass on the order of a few . This is in terms of both the size of the broad line region and the broadening of emission lines (see also Koliopanos 2017 and references therein).…”
Section: Observations Past and Futurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the selection bias of more luminous host galaxies targeted for spectroscopy in the SDSS sample (see, e.g., discussions by Greene & Ho 2004 and Barth, Greene, & Ho 2008), the spectral and spatial resolution of telescopes (like the 5 m telescope used in the Palomar survey) lies right at the threshold of detecting the signatures of a slowly accreting black hole with a mass on the order of a few . This is in terms of both the size of the broad line region and the broadening of emission lines (see also Koliopanos 2017 and references therein).…”
Section: Observations Past and Futurementioning
confidence: 99%
“…However, combining the different methods provides a more robust average prediction. Recently, Koliopanos et al (2017) combined IR, optical, and FUV observation of LLAGN and the M - L , M - PA , M - n sph relations, along with X-ray and radio observations of the accreting central black hole and employing a well-known relation between the radio luminosity ( , 5 GHz), the X-ray luminosity ( , 0.5–10 keV), and the black hole mass (the ‘fundamental plane of black hole activity’: Merloni, Heinz, & di Matteo 2003), to estimate the SMBH mass of candidate LLAGN and probe the consistency between the relations in the low mass regime. The authors demonstrated that the different methods yielded consistent results in the low mass regime.…”
Section: Observations Past and Futurementioning
confidence: 99%
“…In PBH cluster mechanism, such quasars can be formed as a result of accretion of seed PBH [26,43,62,[80][81][82]. The mass of the seed PBH is defined by cluster's formation considered above and its subsequent evolution.…”
Section: Supermassive Black Holesmentioning
confidence: 99%
“…[98][99][100] for relevant discussions for LISA and the third-generation ground GW observatories). Meanwhile, those seed BHs that failed to grow into massive and supermassive BHs may be left to become IMBHs in the local Universe [101,102]. While a few IMBH candidates have been reported (see, e.g., [103][104][105]), a solid confirmation is still lacking from electromagnetic observation.…”
Section: Cosmological Structure Formation and Intermediate-mass mentioning
confidence: 99%